THE MODERATING ROLE OF WORK ENVIRONMENT ON TRAINING AND DEVELOPMENT AND EMPLOYEE ENGAGEMENT IN THE NIGERIAN FEDERAL INLAND REVENUE SERVICE - Ikiba, Mina Alfred; Gambo, Nasamu; Ogedengbe, Frank Alaba (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examined the effect of seven training and development (T&D) dimensions—orientation, compliance, leadership, technical, quality assurance, team, and diversity training—on employee engagement (proxied by job satisfaction) within the Nigerian Federal Inland Revenue Service (FIRS), and investigated the moderating role of the work environment. Grounded in the Job Demands-Resources (JD-R) model, the study adopted a cross-sectional survey design with a sample of 411 employees drawn from a population of 5,250 across 12 states representing Nigeria's six geopolitical zones. Structural Equation Modelling (SEM) using ADANCO software was employed for data analysis. Findings revealed that work environment (β = 0.430, p < 0.001), diversity training (β = 0.479, p < 0.001), and team training (β = 0.159, p < 0.001) were the strongest positive predictors of job satisfaction, with technical training showing a modest but significant effect (β = -0.066, p = 0.046). Orientation, compliance, leadership, and quality assurance training were not statistically significant. The model explained 72.89% of variance in job satisfaction (R² = 0.7289), but work environment did not significantly moderate any T&D–satisfaction relationships. The findings challenge conventional assumptions that all training types equally enhance engagement, demonstrating that socially embedded and climate-dependent resources—particularly inclusion, teamwork, and supportive work conditions—are the primary drivers of job satisfaction in public-sector tax administration. The study contributes to JD-R theory by clarifying resource classification and offers practical recommendations for evidence-based training governance in bureaucratic institutions